PENGARUH INVESTOR CONFIDENCE YANG DIMODERASI OLEH TATA KELOLA PERUSAHAAN TERHADAP KEPUTUSAN INVESTASI PADA PERUSAHAAN MANUFAKTUR YANG TERCATAT DI BURSA EFEK INDONESIA - Maya Zatil Aqmar; Said Musnadi (Departemen Manajemen, 2021)
This research examines how corporate governance can reduce asymmetric information which will ultimately foster investor confidence in a company. Investor confidence has a significant influence on investment decisions, investor confidence can affect financing in the company. Therefore this study aims to determine the effect of corporate governance and investor confidence on investment decisions. This study uses panel data, with purposive sampling method in order to obtain a sample of 25 manufacturing companies listed on the Indonesia Stock Exchange during the 2015-2018 period. The analytical method used is OLS. The findings of this study confirm that there is a significant influence of investor confidence in investment decisions in manufacturing companies. Our findings also imply that investment rates are higher in companies with good corporate governance. Good corporate governance practices can improve the oversight function of board members, so it will be sufficient to control the interests of shareholders, so that company managers can make decisions effectively.